Unions and collective bargaining in Australia in 2018. (June 2019) - Bray, Mark; Macneil, Johanna; Spiess, Leslee
There is a storm brewing over the roles of unions and collective bargaining in Australian employment relations. Unions, frustrated with what they see as practical and legislative restrictions on protection of workers' rights, seek to 'change the rules'. Employers, on the other hand, have been successful in restricting or rolling back bargaining rights, supported by their associations, the Coalition government and an assertive interpretation of the Fair Work Act. Add to this the impending federal election and the scene is set for a tempest that could bring industrial relations back to the centre of Australian politics in 2019. The review explores the various elements contributing to the coming storm, including trends in union membership, structure and strategy. It also surveys trends in the number and coverage of collective agreements, wage outcomes and industrial disputes. Two idiosyncractically Australian versions of collective agreement making are also discussed: cooperative bargaining facilitated by the Fair Work Commission and non-union collective agreement making.